Eating Lifestyle Assessment of AgtaDumagats at Brgy.Malinao, Gabaldon, Nueva Ecija, Philippines: A Basis for an Extension Program - May Nerissa S. Lopez, Dr. Marivic N. Villegas (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to document the eating habit/lifestyle of AgtaDumagats in Gabaldon, Nueva Ecija, Philippines. Thus, can be a baseline for further research about their food ways and be a basis for an extension program. Quantitative and qualitative description design of research was used in this study. Respondents were chosen with the use of purposive sampling technique. Collection of data was through the use of survey questionnaire and face to face interview. The respondents of this study were the 80 AgtaDumagats of Malinao. Questionnaire was validated by content validity, referring to the expert on the field and pilot testing to ensure its reliability and validity. As a faculty of Hospitality Management and Director of Extension Services Department of the university, the scenario struck the chord of the researchers to came up with the study of assessing the food culture of AgtaDumagats which for the future research, be a basis for appropriate extension program in which the NEUST can extend to the AgtaDumagats community; in doing so, the Local Government Unit and the academe can work hand in hand in coming up with an intervention program in addressing food insecurity of the indigenous people.